Estimacion de parametros geneticos en una poblacion de maiz tropical - Oyervides G., A.=700 1 Mariaca P., J.M.; De Leon C., H.; Reyes V., M.
(En, Es)
ilus., 7 ref.
Keywords: ZEA MAYS; HEREDABILIDAD; VARIACION GENETICA; MEXICO